Bibliography. (Berlin ;Boston De Gruyter Mouton, 2015)
Frontmatter -- Preface -- Introductory Bibliography -- General Bibliography -- A -- B -- C -- D -- E -- F -- G -- H -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Z -- Contents
In English
Keywords: Religion -- Study and teaching -- History -- 19th century; Religion -- Study and teaching -- History -- 20th century; Religionswissenschaft; RELIGION / General